Edukasi Pangan Lokal dengan Pemberian Olahan Daun Kelor untuk Pencegahan Anemia pada Remaja Putri di SMAS Adhyaksa 1 - Nurita, Suci Rahmani; Julaecha, Julaecha; Nurfitriani, Nurfitriani (3031-8572, 2024)
Anemia in adolescents is still an important topic because it can have short-term and long-term impacts. Many factors influence the occurrence of anemia. One factor that influences the occurrence of anemia is iron deficiency. Moringa leaves contain high levels of iron (Fe) which can be consumed fresh, in the form of tea or capsules and other processed products. Consumption of processed moringa leaves can be an alternative to prevent anemia in adolescent girls. This community service activity was carried out on grade XI students of SMAS Adhyaksa 1, Jambi City. Based on field observations, most adolescents did not know the benefits of moringa leaves and had not consumed moringa leaves. Based on the initial survey, the partner's problem was the problem of knowledge. The purpose of implementing this educational activity is to increase knowledge. PKM activities were carried out from March to August 2024, starting with identifying partner problems and educational activities for adolescent girls. The material was provided through lectures, demonstrations and discussions with participants. Evaluation was carried out using questionnaires in the form of pretests and posttests. This activity was attended by 113 male and female students of SMAS Adhyaksa 1, Jambi City. The results of the evaluation during the education process, participants seemed enthusiastic about the counseling material, participants listened to the counseling carefully and participants asked questions related to unclear material. The results of PKM showed an increase in participant knowledge from before the education activity and after the education activity by 2-3 points.